Insilico screening of therapeutic potentials from Strychnos nux-vomica against the dimeric main protease (Mpro) structure of SARS-CoV-2. Issue 17 (22nd November 2022) - Kumar, Birendra; Parasuraman, P.; Murthy, Thirupathihalli Pandurangappa Krishna; Murahari, Manikanta; Chandramohan, Vivek
Abstract: The novel coronavirus also referred to as SARS-CoV-2 causes COVID-19 and became global epidemic since its initial outbreak in Wuhan, China, in December 2019. Research efforts are still been endeavoured towards discovering/designing of potential drugs and vaccines against this virus. In the present studies, we have contributed to the development of a drug based on natural products to combat the newly emerged and life-threatening disease. The main protease (M Pro ) of SARS-CoV-2 is a homodimer and a key component involved in viral replication, and is considered as a prime target for anti-SARS-CoV-2 drug development. Literature survey revealed that the phytochemicals present in Strychnos nux-vomica possess several therapeutic activities. Initially, in the light of drug likeness laws, the ligand library of phytoconstituents was subjected to drug likeness analysis. The resulting compounds were taken to binding site-specific consensus-based molecular docking studies and the results were compared with the positive control drug, lopinavir, which is a main protease inhibitor. The top compounds were tested for ADME-Tox properties and antiviral activity. Further molecular dynamics simulations and MM-PBSA-based binding affinity estimation were carried out for top two lead compounds' complexes along with the apo form of main protease and positive control drug lopinavir complex, and the results were comparatively analysed. The results revealed that the two analogues of same scaffold, namely demethoxyguiaflavine and strychnoflavine, have potential against M pro and can be validated through clinical studies. Communicated by Ramaswamy H. Sarma